2003
DOI: 10.1261/rna.5220703
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of the 5′ leader of pre-tRNA substrates by the active site of ribonuclease P

Abstract: The bacterial tRNA processing enzyme ribonuclease P (RNase P) is a ribonucleoprotein composed of a ∼400 nucleotide RNA and a smaller protein subunit. It has been established that RNase P RNA contacts the mature tRNA portion of pre-tRNA substrates, whereas RNase P protein interacts with the 5 leader sequence. However, specific interactions with substrate nucleotides flanking the cleavage site have not previously been defined. Here we provide evidence for an interaction between a conserved adenosine, A248 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
148
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(167 citation statements)
references
References 44 publications
12
148
0
Order By: Relevance
“…Our assignment of the chemically active site is further corroborated by the spatial proximity of structural elements implicated in the recognition of the substrate precursors of tRNA. The base of the highly conserved A256 is thought to pair with nucleotide N -1 of the 5Ј-precursor sequence (49,50) and is positioned next to the cleft. Loop L15, shown to be involved in binding the substrate 3Ј-CCA (51), although partially disordered is also within consistent distance to the proposed active site (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our assignment of the chemically active site is further corroborated by the spatial proximity of structural elements implicated in the recognition of the substrate precursors of tRNA. The base of the highly conserved A256 is thought to pair with nucleotide N -1 of the 5Ј-precursor sequence (49,50) and is positioned next to the cleft. Loop L15, shown to be involved in binding the substrate 3Ј-CCA (51), although partially disordered is also within consistent distance to the proposed active site (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has focused on the characterization of the interactions between substrate and PRNA in the ribozyme reaction (Christian et al 1998;Loria and Pan 1998;Christian and Harris 1999;Siew et al 1999;Zahler et al 2003) and demonstrated that the substrate directly contacts the P protein in RNase P (Crary et al 1998;Niranjanakumari et al 1998b). However, less is known about the interactions between the PRNA and the P protein within the holoenzyme complex.…”
Section: Introductionmentioning
confidence: 99%
“…This nucleotide change occurs in a conserved site considered to be important for function (Zahler et al, 2003). An ARU mutation at this position (E. coli position 248) has been shown to be of particular significance to the binding affinity and catalysis relevant to pre-tRNA processing (Zahler et al, 2003). The change in the base at this site, which is otherwise conserved throughout the Bacteria, is consistent with the divergent position of the planctomycetes.…”
Section: Resultsmentioning
confidence: 95%
“…strain 1, has revealed the mutation of a base universally conserved in Archaea and Bacteria (Zahler et al, 2003). Thought to be invariant, A248 has been replaced by a U in these sequences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation